Disaster Risk Management in the Transport Sector : A Review of Concepts and International Case Studies - World Bank (Washington, DC, 2015)
Natural hazards regularly impact the performance of transport systems and their ability to provide safe, reliable, efficient, and accessible means of transport for all citizens, especially in emergency situations. Despite the frequency of natural hazards, and the threat of more extreme and variable weather as a result of climate change, there is still no systematic approach to addressing natural disasters in the transport sector and there is little knowledge that has been disseminated on this topic. This report offers a framework for understanding the principles of resilience in transport. It provides practical examples, gathered from an extensive secondary literature review and interviews, of the measures that transport professional can implement in transport projects.